MEMBRANE LEc EXPRESSION IN BREAST CANCER CELLS - Ya. A. Udalova; N. V. Bovin; P. S. Obukhova; N. V. Shilova; A. M. Kovrigina; A. A. Subbotina; V. V. Timoshenko; O. E. Galanina; Z. G. Kadagidze; V. P. Letyagin; N. N. Tupitsyn (Опухоли женской репродуктивной системы, 2014)
Affine chromatography was used to isolate Lec antibodies from the sera of a healthy female donor with the high titers of these anti- bodies, which were labeled with biotin. The study enrolled 51 patients with primary breast cancer (BC). Antigen expression was found by immunohistochemistry and flow cytometry. With these two techniques being used, the detection rate of Lec expression in BC cells was 65% (33/51); the antigen was most frequently found by flow cytometry as compared with immunohistochemistry: 72 and 58% of cases, respectively.